2016
DOI: 10.1136/heartjnl-2016-309993
|View full text |Cite
|
Sign up to set email alerts
|

Screening for atrial fibrillation in 13 122 Hong Kong citizens with smartphone electrocardiogram

Abstract: Objective The purpose of this study was to assess the feasibility of community screening for atrial fibrillation (AF) using a smartphone-based wireless single-lead ECG (SL-ECG) and to generate epidemiological data on the prevalence and risk factors of AF in Hong Kong.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
52
4
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(67 citation statements)
references
References 29 publications
9
52
4
2
Order By: Relevance
“…Several studies have shown the efficacy of these devices for atrial fibrillation screening in populations at risk (table 3). 731323334353637383940…”
Section: Applications Of Newer Detection Methodsmentioning
confidence: 99%
“…Several studies have shown the efficacy of these devices for atrial fibrillation screening in populations at risk (table 3). 731323334353637383940…”
Section: Applications Of Newer Detection Methodsmentioning
confidence: 99%
“…The early diagnosis of AF may lead to individualised lifestyle intervention and anticoagulation, and these steps may be associated with a reduction in complications and healthcare costs. The development of hand‐held electrocardiogram (ECG) screening devices, has increased the feasibility of AF screening. Appropriate selection of patients for screening is of critical importance; the development of a risk assessment score, based on the link between AF and clinical risk factors, is an important component of identifying individual patients at risk.…”
Section: Introductionmentioning
confidence: 99%
“…Various screening approaches have been proposed in papers previously published in Heart , including use of smartphone ECGs in the general population4 and handheld ECG devices in hospitalised geriatric patients,5 to name just a few 6. Linker and colleagues7 propose a new risk score based on clinical variables, without an ECG, to identify patients at risk of AF development.…”
mentioning
confidence: 99%